EPISTEMOLOGY IN THE PERSPECTIVE OF ISLAMIC PHILOSOPHY OF SCIENCE: THE INTEGRATION OF REVELATION, INTELLECT, AND SPIRITUAL EXPERIENCE IN THE ISLAMIC INTELLECTUAL TRADITION - Jemmy Harto; Ilzamudin Ma’mur; Mufti Ali; Umdatul Hasanah (Program Studi Manajemen Pendidikan Islam, 2026)
The development of modern science tends to be dominated by an epistemology that places ratio and empirical experience as the primary foundations of truth, thereby marginalizing transcendent dimensions and normative values. This condition creates the need for a more comprehensive epistemological framework. This paper aims to examine epistemology from the perspective of Islamic philosophy of science by emphasizing the integration of revelation, intellect, and spiritual experience as the foundations for the acquisition and validation of knowledge within the Islamic intellectual tradition. This study employs a qualitative approach through library research, using conceptual analysis of literature on philosophy of science as well as classical and contemporary Islamic thought. The findings indicate that Islamic epistemology is holistic and theocentric, in which revelation functions as the primary normative source, reason acts as the rational instrument, and empirical experience serves as a means of verifying the reality of the natural world.The integration of these three elements forms an epistemological framework that not only emphasizes rational and empirical truth but also relates it to ethical and metaphysical dimensions. Therefore, Islamic epistemology provides a theoretical contribution to the development of the philosophy of science and to the formulation of a scientific paradigm oriented toward truth and human well-being within the context of contemporary knowledge